Engineering of polymer-based grafts with cells derived from human nucleus pulposus tissue of the lumbar spine - Hegewald, Aldemar Andres; Enz, Andreas; Endres, Michaela; Sittinger, Michael; Woiciechowsky, Christian; Thomé, Claudius; Kaps, Christian (Journal of tissue engineering and regenerative medicine, 2011)
Intervertebral disc degeneration is considered a major source of low back pain. We therefore examined an absorbable polyglycolic acid (PGA) biomaterial for its utility to support disc tissue regeneration. Microdiscectomy for lumbar disc herniation was performed in six patients. Intervertebral disc cells were isolated and in vitro cell expansion was accomplished using human serum and FGF2. In a fibrin-hyaluronan solution, disc cells were loaded on PGA scaffolds and cultured for 2 weeks. Formation of disc tissue was documented by histological staining of the extracellular matrix as well as gene expression analysis of typical disc marker genes. The use of human serum and FGF2 ensures efficient isolation and expansion of human disc cells. During this phase, dedifferentiation of the disc cells was observed. Subsequent 3D tissue culture of disc cells in PGA scaffolds, however, is accompanied by the induction of typical disc marker genes, resulting in tissue containing glycosaminoglycans and collagens. Propidium iodide/fluorescein diacetate (PI/FDA) staining documented that 3D assembly of disc cells in PGA scaffolds allows prolonged culture and high viability of disc cells. Disc cells from tissue of the nucleus compartment can be reliably isolated and expanded in vitro with FGF. In combination with a fibrin-hyaluronan solution and loaded on a PGA scaffold, disc cells from expansion culture commence a redifferentiation process. PGA-based scaffolds could be useful as temporal matrices for regenerative disc repair approaches. Copyright © 2010 John Wiley & Sons, Ltd.